(untitled) (Experimental biology, 2010)
Optimization of agrobacterial pollen transformation method for cotton variety Kazakhstan selection has been carried out by the use of reporter GUS- and selective marker nptII- genes. Transgenic plants of Maktaaral 4005 with nptII- и GUS- genes have been obtained.